Polytetrafluoroethylene tape spacer for direct splinted teeth-supported provisional restoration: A dental technique - Hayam Alfallaj; Faris Z. Jamjoom; Abdulaziz A. Alzaid; Hatem Alqarni (Heliyon, 2023)
Provisional restoration is essential for function, esthetics, occlusion, and tissue health. However, when multiple teeth are involved, making a direct splinted provisional restoration could be challenging due to the combined undercuts between the prepared teeth. This article describes a dental technique using polytetrafluoroethylene (PTFE) tape as a spacer to fabricate a splinted provisional restoration for multiple prepared teeth. The PTFE tape spacer will compensate for discrepancies in the path of insertion between prepared teeth, thus facilitating the removal of the direct splinted provisional restoration intact.